A four-stage management mode of safe production affairs. (November 2020) - Xie, Hongyan; Qi, Deyu
Abstract: Safety production management system is widely used at present. The current safety production management system only improves some aspects of production safety, but it is not suitable for all engineering management, and there is no good solution in the engineering management mode. In this paper, a four-stage management mode based on safety production affairs is proposed, which plays a good role in the engineering management of safety production. The intelligent safety assessment system has a good effect.